Sustainable water reuse in food production: risks of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli and antimicrobial resistance gene release from tertiary-treated reclaimed water - Truchado, Pilar; Oliveira, Márcia; Cordero-García, Rebeca; Abellán Soler, Manuel; Rancaño, Amador; García, Francisca; Álvarez-Ordóñez, Avelino; Allende, Ana (Frontiers in Microbiology, 2025)
Wastewater reuse for agricultural irrigation is increasingly essential, but it carries potential public health risks due to the dissemination of antimicrobial resistance (AMR). This study evaluates the effectiveness of four tertiary wastewater treatment technologies—peracetic acid (PAA), PAA combined with low-intensity ultraviolet-C (PAA/UV Low), high-intensity UV-C (UV High), and ultrafiltration (UF)—in reducing extended-spectrum β-lactamase-producing Escherichia coli (ESBL-E. coli) and antimicrobial resistance genes (ARGs) in reclaimed water used for irrigation. The relative abundance of the genes, normalized to the 16S RNA gene present in the water samples, was then estimated to assess whether there is an amplification of these genes during the reuse process in the wastewater treatment plant (WWTP). The results indicate that while all treatments significantly reduced ESBL-E. coli (≥3 logs cfu/100 mL) and ARGs (≥ 1.5 logs gc/100 mL), complete elimination was not achieved in any WWTP. Among the treatments, UF demonstrated the highest removal efficiency (≈4 log gc ARG/100 mL), against ARGs, followed by UV High (≈3 log gc ARG/100 mL), whereas PAA and PAA/UV Low were less effective (≈2 log gc ARG/100 mL). The study also found that while absolute ARG levels were reduced, their relative abundance remained stable or showed minimal decline, suggesting a persistent environmental reservoir of resistance genes. Among the ARGs analyzed, the most frequently detected were associated with tetracyclines (tetW, tetA), quinolones (qnrB, qnrS), and sulfonamides (sul1, sul2), highlighting potential public health concerns. Moreover, multidrug-resistant (MDR) ESBL-E. coli isolates were present across all WWTPs, exhibiting resistance to β-lactams, quinolones, tetracyclines, and sulfonamides. Nevertheless, notably low levels of resistance to last-resort antibiotics (tigecycline, colistin, and meropenem) were observed. These findings underscore the critical role of tertiary treatments in mitigating antimicrobial resistance (AMR) risks in water reuse systems. However, the persistence of ARGs in effluents suggests that current WWTP processes require further optimization.